2015
DOI: 10.1188/15.cjon.e126-e130
|View full text |Cite
|
Sign up to set email alerts
|

Use of Videos as Supplemental Education Tools Across the Cancer Trajectory

Abstract: Videos deliver material in a way that is flexible and often familiar to patients. For example, delivery can occur via smartphone, electronic health record, computer, DVD, or television, and it does not require reading or a high level of literacy. Healthcare providers in oncology settings should consider establishing a process for instructional video development as part of a multimedia patient education library.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Frentsos discussed the use of videos as education materials among cancer survivors, emphasizing that the use of videos does not require a high level of literacy and can be delivered via smartphone, DVD, television, or computer. 17 Other authors have found that among older adult populations known to have limited health literacy, the development of specific tailored materials can improve patient understanding. 18 An investigation reported that among five categories of information source use (mass media, Internet and print media, support organizations, family and friends, and healthcare providers), higher education predicted the increased use of all source categories except mass media.…”
Section: Discussionmentioning
confidence: 99%
“…Frentsos discussed the use of videos as education materials among cancer survivors, emphasizing that the use of videos does not require a high level of literacy and can be delivered via smartphone, DVD, television, or computer. 17 Other authors have found that among older adult populations known to have limited health literacy, the development of specific tailored materials can improve patient understanding. 18 An investigation reported that among five categories of information source use (mass media, Internet and print media, support organizations, family and friends, and healthcare providers), higher education predicted the increased use of all source categories except mass media.…”
Section: Discussionmentioning
confidence: 99%
“…Information materials must contain scientifically reliable information and be presented in a form that is acceptable and useful to patients. Education materials can be formatted in different media including video (Abed, Himmel, Vormfelde, & Koschack, 2014; Frentsos, 2015; Wang et al, 2015), audio (Kekecs, Jakubovits, Varga, & Gombos, 2014), iPod (Denizard-Thompson, Singh, Stevens, Miller, & Wofford, 2012), handheld PC (Alur, Cirelli, Goodstein, Bell, & Liss, 2010), printed media sources, or even mass media sources (Buchbinder & Jolley, 2005; Gerber et al, 2005; Makoul et al, 2009; Treweek, Glenton, Oxman, & Penrose, 2002). However, no studies were found to test audio-based patient education (Thygesen, Nicolaisen, & Mogensen, 2015).…”
mentioning
confidence: 99%
“…However, no studies were found to test audio-based patient education (Thygesen, Nicolaisen, & Mogensen, 2015). Teaching strategies identified are traditional lectures, discussions, simulated games, computer technology, online, written material, audiovisual sources, verbal recall, demonstration, role-playing, and other methods have become available (Bobian et al, 2017; Free et al, 2013; Frentsos, 2015; Friedman, Cosby, Boyko, Hatton-Bauer, & Turnbull, 2011; Gulati, Nawaz, & Pyrsopoulos, 2016; Joseph et al, 2016; Schneider et al, 2016; Stribling & Richardson, 2016; Tang, Chan, So, & Leung, 2014). In American, online Personal Health Records (PHR) is getting patient welcome (Schickedanz et al, 2013; Zarcadoolas, Vaughon, Czaja, Levy, & Rockoff, 2013).…”
mentioning
confidence: 99%
“…To limit subjectivity between the 2 reviewers, the grading system for each question was standardized in advance, based on the DISCERN manual. The total DISCERN score spans between 16 and 80 and breaks down as excellent (68-80), good (55-67), fair (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), poor (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and very poor (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discern Instrumentmentioning
confidence: 99%